2019
DOI: 10.29252/ibj.23.6.423
|View full text |Cite
|
Sign up to set email alerts
|

Alu DNA Polymorphism of Human Tissue Plasminogen Activator (tPA) Gene in Diabetic Jordanian Patients Patients

Abstract: Background:Hypercoagulability and hypofibrinolysis are among the symptoms exhibited by diabetic patients. Our study aimed to address the polymorphic nature of Alu DNA fragment in the human tissue plasminogen activator gene within diabetes mellitus (DM) Jordanian patients.Methods:Genomic DNA was isolated from 76 DM patients and 60 non-diabetic Jordanian individuals, and the Alu fragment was amplified using PCR. Results:The results showed that 80% of the non-diabetic Jordanian subjects were homozygotes for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…5,6 It has been reported that subjects homozygous for the Ins allele have a significantly higher rate of t-PA release than both heterozygotes and homozygous subjects for the Del allele. 5 The Del allele is reversibly associated with the risk of several complex diseases, including recurrent pregnancy loss, 6 diabetes mellitus, 7 myocardial infarction 8 and schizophrenia. 9 It should be noted that t-PA is expressed in retina and plays a key role in the eye development.…”
Section: Genotypingmentioning
confidence: 99%
“…5,6 It has been reported that subjects homozygous for the Ins allele have a significantly higher rate of t-PA release than both heterozygotes and homozygous subjects for the Del allele. 5 The Del allele is reversibly associated with the risk of several complex diseases, including recurrent pregnancy loss, 6 diabetes mellitus, 7 myocardial infarction 8 and schizophrenia. 9 It should be noted that t-PA is expressed in retina and plays a key role in the eye development.…”
Section: Genotypingmentioning
confidence: 99%